2013
DOI: 10.1097/ogx.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

Activity Restriction Among Women With a Short Cervix

Abstract: OBJECTIVE-To estimate determinants of and outcomes associated with activity restriction among women with a short cervix.METHODS-This was a secondary analysis of a randomized trial of 17-α hydroxyprogesterone caproate for prevention of preterm birth among nulliparous women with singleton gestations and cervices less than 30 mm by midtrimester ultrasonography. Women were asked weekly whether they had been placed on pelvic, work, or nonwork rest. "Any activity restriction" was defined as being placed on any type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…In a secondary analysis of an RCT of 17‐α hydroxyprogesterone caproate among nulliparous women with singleton gestations and mid‐trimester TVS‐CL < 30 mm, Grobman et al . showed that activity restriction increased the risk of PTB < 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In a secondary analysis of an RCT of 17‐α hydroxyprogesterone caproate among nulliparous women with singleton gestations and mid‐trimester TVS‐CL < 30 mm, Grobman et al . showed that activity restriction increased the risk of PTB < 37 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review from 2014 (34) and subsequent study, physical rest could not be shown to reduce the preterm birth rate. Two studies of pregnant women at risk of preterm birth even found a 2.1-2.4-fold increase in the preterm birth rate <34 weeks' gestation or <37 weeks' gestation (aOR: 2.37; [1.60; 3.53]) (35,36).…”
Section: Work Load Physical Rest Bed Restmentioning
confidence: 99%
“…The analysis by Werner et al 19 is based in large part on probabilities reported in the randomized trial by Fonseca et al, 12 but Werner et al 19 performed their cost analysis using only singleton pregnancies without a history of previous preterm birth, and the subgroup with greatest benefit from cervical length screening and treatment with progesterone in the trial by Fonseca et al 12 was the group of women with a history of previous preterm birth. In addition, baseline cost estimates in the analysis by Werner et al 19 were $0 for hospital admission for short cervix and $0 for loss of productivity secondary to bed rest; therefore, it will be important to avoid hospitalization and activity restrictions in women with short cervices to realize the savings described by Werner et al 19 Avoidance of activity restrictions is particularly important as activity restriction has been shown NOT to reduce the rate of preterm birth in asymptomatic women with a short cervix, 20 while there is strong evidence that there are detrimental effects to the mother and her family when the gravid patient is placed on activity restriction. In addition, baseline cost estimates in the analysis by Werner et al 19 were $0 for hospital admission for short cervix and $0 for loss of productivity secondary to bed rest; therefore, it will be important to avoid hospitalization and activity restrictions in women with short cervices to realize the savings described by Werner et al 19 Avoidance of activity restrictions is particularly important as activity restriction has been shown NOT to reduce the rate of preterm birth in asymptomatic women with a short cervix, 20 while there is strong evidence that there are detrimental effects to the mother and her family when the gravid patient is placed on activity restriction.…”
Section: Cost-effectiveness Analyses Investigating Universal Cervicalmentioning
confidence: 99%